Bandas de música, escolas de vida - Lima, Ronaldo Ferreira de (2006)
The focus of this dissertation is to understand the child and youth musical learning trajectory by using two philharmonic orchestras from Seridó, an area in the interior of Rio Grande do Norte. One is called the Hermann Gmeiner Philharmonic Orchestra of Aldeias Infantis SOS Project from Caicó, and the other is the 24 de Outubro Philharmonic Orchestra from Cruzeta. It emphasizes the singular relationship between the band s master and his students, based on a permanent interaction with tradition, creativity and change, resulting from a shared educational process. The idea that unites the work of these two communities is the gamble about the individual's formation as a complex human being, which it is not just concerned with the learning of a musical instrument, but is, more importantly, an educational process capable of facilitating the discovery of the self, others and society. The history and the course of the musical education of these two experiences were facilitated using a base of semi-structured interviews of the bands masters, students and people from two municipal districts. Their history is understood through analysis of the band s pictures and the theoretical-social approach is governed by the complexity idea expressed by Edgar Morin. For the author, complex means to `weave together`; therefore it is multidimensional, and it creates a dialogue about several domains and aspects that occur on the same phenomenon. The complex always supposes creativity and the relationship between the subject s reason and affectivity